DESIGNING COMPUTER ASSISTED LANGUAGE LEARNING SOFTWARE EVALUATION - Saleh Rosana Emy (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2018)
The use of computer to assist learning has increased significantly through more than three decades.  However, the use of the instrument is still becoming a problem among teachers and educators. This paper discusses the evaluation criteria in selecting Computer Assisted Language Learning (CALL) software in language and skill development for ESL/EFL. The CALL evaluation criteria proposed in this paper is aimed to assist English language teachers to determine good quality CALL software used in classroom activity. CALL has proven its benefits for three aspects:  programming consideration, educational design, and easy for use. A checklist describing evaluation aspects of the CALL is provided in this paper.